Systematic review of memory assessment in virtual reality: evaluating convergent and divergent validity with traditional neuropsychological measures - Mancuso, Valentina; Sarcinella, Eleonora Diletta; Bruni, Francesca; Arlati, Sara; Di Santo, Simona Gabriella; Cavallo, Marco; Cipresso, Pietro; Pedroli, Elisa (Frontiers in Human Neuroscience, 2024)
Introduction The evaluation of memory is a crucial aspect of both cognitive research and clinical applications, as it offers valuable insights into an individual’s cognitive wellbeing and performance. Conventional neuropsychological assessments represent the established method for assessing different aspects of memory. Recent technological advancements, specifically in the field of virtual reality (VR), have introduced novel methods for evaluating memory. Objective This systematic review aims to examine the current state of memory assessment using VR technologies, assessing the degree of convergence and divergence between VR-based memory assessments and conventional neuropsychological tests. Method A systematic review of the literature was conducted searching PubMed, PsycINFO, Web of Science databases, leading to the incorporation of 24 studies. Studies were grouped according to the examined memory domain (episodic, prospective, spatial domain). Convergence and divergence validity were examined for each, and information on software and hardware features was collected. Results This review demonstrates a notable alignment between VR-based memory assessments and conventional neuropsychological tests. Moreover, VR tasks have shown to exhibit associations with executive functions and overall cognitive performance. The inclusion of various ecological contexts, such as residential environments, commercial establishments, and simulated scenarios, serves to augment the ecological validity of memory evaluations conducted in VR. Discussion The findings indicate that VR assessments demonstrate a functional perspective by effectively capturing the dynamic relationship between memory, executive functions, and overall cognitive performance. Nevertheless, it is imperative to acknowledge and tackle certain constraints that may hinder the widespread adoption and utilization of VR tasks. These limitations encompass factors such as restricted accessibility to VR tasks and the presence of heterogeneity in VR hardware and software. The dynamic and ever-changing nature of VR technology presents a range of potential avenues for future investigation and utilization in the domain of memory evaluation.